Isu Kebijakan Trans Pacific Partnership dalam Kampanye Calon Presiden Amerika 2016 dan Relevansinya Bagi Indonesia - Imron Rosyadi Hamid (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
Since the signing of the Trans Pacific Partnership (TPP) by the Obama Administration in February 2016, anti- and pro-TPP groups have emerged during the United States presidential campaign. Both Hillary Clinton and Donald Trump have voiced their voice against the Trans Pacific Partnership agreement. This study describes the role of party platforms, both Republican Party Platform 2016 and Democratic Party Platform 2016 as a scale to find important information related to the Trans Pacific Partnership issue during the 2016 United States presidential campaign. On the other hand, after his meeting with President Obama in October 2015 in the United States, President Joko Widodo said that Indonesia was ready to join the Trans Pacific Partnership. By using Dependency Theory, this study will explain why a free trade agreement such as the Trans Pacific Agreement must be measured by national interests before being implemented as a government policy.